A small, low-grade rectal neuroendocrine tumor with lateral pelvic lymph node metastasis: a case report - Seonhui Shin; Young-In Maeng; Seyun Jung; Chun-Seok Yang (Annals of Coloproctology, 2022)
Rectal neuroendocrine tumors (NETs) are typically small lesions that are confined to the submucosa and have favorable behavior at the time of diagnosis. Local endoscopic or surgical resection is recommended because lymph node metastasis is very rare. In this report, we present the case of a 36-year-old male presenting with an incidentally found rectal mass during screening colonoscopy. Pathologic examination of the primary tumor revealed a 9-mm grade 1 NET with submucosal invasion and no significant aggressive factors except for central ulceration. However, radiologic studies revealed a suspected 2.6-cm mesorectal lymph node metastasis and multiple left internal iliac lymph node metastases. We performed laparoscopic intersphincteric resection with left lateral pelvic lymph node dissection. The final pathologic report revealed a metastatic lymph node with low grade, low mitotic count, and low Ki-67 index. We describe an overview of lymph node metastasis of rectal NETs focusing on lateral pelvic lymph node metastasis.